Public finance : for M.A. and M. Com. students of Indian universities - Bhatia, H. L. (New Delhi : Vikas, 2000)
This books explains the basic nature of any lies in the scarcity of its productive resources in relation to its wants.
Includes bibliography
osc 3/12/2018
Loans
Keywords: Finance, Public